Recent Progress in Flow Control for Practical Flows Results of the STADYWICO and IMESCON Projects - Doerffer, Piotr; Barakos, George N.; Luczak, Marcin M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book explores the outcomes on flow control research activities carried out within the framework of two EU-funded projects focused on training-through-research of Marie Sklodowska-Curie doctoral students. The main goal of the projects described in this monograph is to assess the potential of the passive- and active-flow control methods for reduction of fuel consumption by a helicopter. The research scope encompasses the fields of structural dynamics, fluid flow dynamics, and actuators with control. Research featured in this volume demonstrates an experimental and numerical approach with a strong emphasis on the verification and validation of numerical models. The book is ideal for engineers, students, and researchers interested in the multidisciplinary field of flow control. Provides highly relevant and up-to-date information on the topic of flow control; Includes assessments of a wide range of flow-control technologies and application examples for fixed and rotary-wing configurations; Reinforces reader understanding with case studies based on real aircraft; Explains modelling methodologies and strategies for flow control of separated flows and numerous experimental measurement results on the real structures; Illustrates new developments in actuator technology.
Part 1: Introduction to Flow control Technology -- Introduction and Literature Survey -- Part 2: Design of modern Gurney Flap -- CFD Method for Modelling Gurney Flaps -- Performance Enhancement of Rotors in Hover Using Fixed Gurney Flaps -- Alleviation of Retreating Side Stall Using Active Gurney Flaps -- Effect of Gurney Flaps on Overall Helicopter Flight Envelope -- Active Gurney Flap Unit -- Gurney Flap Force Calculation -- Part 3: Design of Rod Vortex Generator -- Investigation of Vortex Generators on Channels and Airfoils -- Implementation of Rod Vortex Generators on Helicopter Rotor Blades in Hover and Forward Flight Conditions -- Retractable Rod Vortex Generator -- Part 4: Important issues in Synthetic Jet Design -- Numerical Simulation of a Synthetic Jet Actuator for Active Flow Control -- Introduction to the Synthetic Jet Flow Control and Drag Reduction Techniques -- Experimental results of Synthetic Jet Wind Tunnel Tests -- Part 5: Multi Physics Co-Simulation Methods -- Fluid-Structure Interaction Simulation -- Analysis and Optimization of Flow Around Flexible Wings and Blades Using the Standard Co-Simulation Interface MpCCI -- Numerical Simulation of Air Flow and Acoustic Field Around a Passenger Car Model Using Euler Approach and Hybrid Meshing -- Computation of Rotorcraft Stability Derivatives Using the Discrete Adjoint Method -- Part 6: Structural Dynamics of Blades and Components -- Dynamics of the Synthetic Jet Actuator Investigation by the Numerical and Experimental Approach -- Thermal Synthetic Jet Actuator Investigation by Experimental Approach -- Modal Analysis of PZL-W-3/W-3A Sokol Main Rotor -- Strain Modal Analysis of the Blade -- Uncertainty Quantification of the Main Rotor Blades Measurements -- Temperature Compensation Methods for Elastic Wave Based SHM.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Aerospace engineering; Astronautics; Control engineering; Robotics; Automation; Energy policy; Energy and state; Fluid mechanics; Multibody Systems and Mechanical Vibrations; Aerospace Technology and Astronautics; Control and Systems Theory; Control, Robotics, Automation; Energy Policy, Economics and Management; Engineering Fluid Dynamics